Confrontation Analysis as an Alternative Model in International Relations: From Chinese Civil War to Korean War - Manuhutu, Khrisna Ariyanto; Sudirman, Arfin; Setiabudi, Widya; Hakiki, Falhan (Andalas Journal of International Studies (AJIS), 2022)
In analyzing confrontation, academic studies in the field of International Relation are highly associated with conventional narrative approaches. Unfortunately, exclusive and excessive use of an approach in the field may hinder the academic development in the field. Earlier studies show that cross-fertilization internal and external approaches can promote scientific progress in the field. This study aims to promote the use of confrontation analysis, an analysis tool that is considered as external to the field of international relations. There are some studies in the field of international relations that utilize confrontation analysis in conflict modelling. Nonetheless, these studies are limited only to the cases of western hemisphere. This study focuses on the implementation of confrontation analysis in the conflict in East Asia region, i.e. Chinese civil war and Korean war. These cases are selected due to the abundant available information on these conflicts and the knowledge on these conflicts has matured. This study shows that confrontation analysis is able to explain the increase of escalation and its downturn during the conflict.